2004
DOI: 10.1038/sj.npp.1300430
|View full text |Cite
|
Sign up to set email alerts
|

Altered 5-HT2A Receptor Binding after Recovery from Bulimia-Type Anorexia Nervosa: Relationships to Harm Avoidance and Drive for Thinness

Abstract: Several lines of evidence suggest that a disturbance of serotonin neuronal pathways may contribute to the pathogenesis of anorexia nervosa (AN) and bulimia nervosa (BN). This study applied positron emission tomography (PET) to investigate the brain serotonin 2A (5-HT 2A ) receptor, which could contribute to disturbances of appetite and behavior in AN and BN. To avoid the confounding effects of malnutrition, we studied 10 women recovered from bulimia-type AN (REC AN-BN, 41 year normal weight, regular menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 124 publications
5
107
0
3
Order By: Relevance
“…The well-known distortion of body image in individuals with AN may suggest abnormalities of circuits through the postulated 'self' networks. In line with this, left parietal cortical activation has previously been linked to AN womens' evaluation of body image (115,116).…”
Section: Body Image Distortionsupporting
confidence: 55%
See 1 more Smart Citation
“…The well-known distortion of body image in individuals with AN may suggest abnormalities of circuits through the postulated 'self' networks. In line with this, left parietal cortical activation has previously been linked to AN womens' evaluation of body image (115,116).…”
Section: Body Image Distortionsupporting
confidence: 55%
“…These studies reported a hyper-responsiveness in brain areas belonging to the frontal visual system and the attention network (BA 9) as well as inferior parietal lobule (BA 40), including the anterior part of the intraparietal (IPL) sulcus. Bailer (116) reported negative relationships between 5-HT 2A receptor activity and the Eating Disorder Inventory Drive for Thinness scale in the left parietal cortex and other regions. It is intriguing to raise the possibility that left hemisphere disturbances of this pathway may contribute to body image distortion.…”
Section: Body Image Distortionmentioning
confidence: 99%
“…Other imaging studies have found altered serotonergic activity in similar cingulate regions in BN subjects. 11,20 Moreover, Uher et al 21 reported that pictures of food increased activity in the ACC and other regions in BN subjects compared with CW.…”
Section: Resultsmentioning
confidence: 99%
“…86 In women recovered from bulimia-type AN, [ 18 F]altanserin binding potential and drive for thinness were negatively correlated in several cortical regions, suggesting that altered 5-HT neuronal system activity persisted. 87 Given that different measures have been used to capture these cognitive features, further work is required to increase the reliability and validity of these measures before conclusions can be drawn about their potential status as an eating disorder endophenotype, including the degree to which they are influenced by genetic factors.…”
Section: Cognitive Featuresmentioning
confidence: 99%